A review of the environmental and health implications of recycling mine tailings for construction purposes in artisanal and small-scale mining communities. (March 2022) - Velásquez, José R.; Schwartz, Michelle; Phipps, Laura M.; Restrepo-Baena, Oscar Jaime; Lucena, Juan; Smits, Kathleen M.
Abstract: Technical advancements in mine tailings recycling have led to the production of construction products such as bricks, cement, road pavers, and mortars in artisanal and small-scale mining (ASM) communities. Although such efforts show promise, the environmental, health, and social implications of such practices are often overlooked by stakeholders including researchers, miners, and community members. This paper summarizes and evaluates the environmental and health implications of mine tailings recycling activities (MTRAs) in ASM. A comprehensive review was conducted using both academic and gray literature to analyze the current state of practice linked with environmental and health considerations. From the fifty-three analyzed MTRAs, twenty-three articles considered aspects of environmental concerns, and three studied aspects of health in mine tailings recycling processes. When included, environmental and health considerations mainly focused on toxicity leaching protocols or analyzing health risks and exposure routes of facilities constructed out of mine tailings construction materials. Results suggest that studies mostly focus on lab-scale experiments evaluating the material properties of the MTRAs products and have limited consideration of field application and social concerns. No study considered environmental, health and social implications in unison. To comprehensively address these concerns, a Comprehensive Approach to Recycling Tailings (CART) framework is proposed that can assist communities and researchers to better understand the possible environmental and health implications of MTRAs and to incorporate such understanding into practice.